2011
DOI: 10.1051/epjap/2011110220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular semiconductor-doped insulator (MSDI) heterojunctions as new transducers for chemical sensors

Abstract: This article describes a new principle of transduction involving an heterojunction between a Molecular Semiconductor and a Doped Insulator (MSDI). Herein, we report on an MSDI-based sensor featuring an heterojunction between a lutetium bisphthalocyanine (LuPc2), which acts as Molecular Semiconductor (MS) and a thin film of Doped Insulator (DI) made of substituted or fluorinated copper phthalocyanine (CuFnPc, where n = 0, 8, 16). Previously, we reported the peculiar effect of the heterojunction on the MSDI's el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…There is no additional band at higher wavelengths, indicating the absence of significant charge transfer between the two layers, as described previously for Cu(F 16 Pc)/LuPc 2 heterostructure [67]. The Raman spectra of the bilayer heterostructures and individual phthalocyanines in them coated on glass substrate were recorded between 500 and 1700 cm -1 .…”
Section: Electronic Absorption and Raman Spectroscopiessupporting
confidence: 60%
“…There is no additional band at higher wavelengths, indicating the absence of significant charge transfer between the two layers, as described previously for Cu(F 16 Pc)/LuPc 2 heterostructure [67]. The Raman spectra of the bilayer heterostructures and individual phthalocyanines in them coated on glass substrate were recorded between 500 and 1700 cm -1 .…”
Section: Electronic Absorption and Raman Spectroscopiessupporting
confidence: 60%
“…The apparent energy barrier U th , deduced by extrapolating the tangent to the curve at high bias to abscissa is estimated as 6.6 V and 6. in agreement with the large difference in the energies of frontiers orbitals of LuPc 2 and Cu(F 8 Pc), which makes difficult for charges hopping from LuPc 2 orbitals to Cu(F 8 Pc) at the interface. 46 On the other hand, LUMO level of Cu(F 16 Pc) aligns well with the SOMO of LuPc 2 , facilitating easier charges hopping at the interface. Notably, in both heterojunctions, U th decreases upon light exposure, indicating that charge injection from electrode to interface becomes easier.…”
Section: Electrical Properties Of Organic Heterojunction Devicesmentioning
confidence: 96%
“…The optical absorption spectra confirmed that after deposition, the devices contain both materials ( Table 1 ). Both heterostructures exhibit the same peak at 669 nm, which belongs to LuPc 2 and corresponds to its Q-band ( Figure 4 ) [ 36 ]. The bands at 605 and 604 nm correspond to the so-called “blue vibration band” of LuPc 2 .…”
Section: Resultsmentioning
confidence: 99%